Resource utilization and direct medical costs of chronic hepatitis C in Thailand: A heavy but manageable economic burden - Satawat Thongsawat (2018)
Objective: To estimate the cost for the management of chronic hepatitis C (CHC) and related morbidities by using a payer perspective in Thailand. Methods: Data elements were extracted from medical records of 542 patients newly diagnosed with CHC in five tertiary care hospitals across Thailand. All patients were divided into five health states: noncirrhotic CHC, hepatitis C virus (HCV)-related compensated cirrhosis, HCV-related decompensated cirrhosis, HCV-related hepatocellular carcinoma, and HCV-related liver transplantation. Resource utilization data for each patient during a 12-month follow-up study period were compiled, and reference prices published by the Thai government were used to estimate the cost for each health state. The average cost was calculated and categorized into various groups, for example, laboratory and diagnostic tests, procedures, medication, and hospitalization. Results: The average number of outpatient visits per patient was approximately six visits in all cohorts. The HCV-related hepatocellular carcinoma and liver transplantation cohorts had a higher average number of inpatient admissions per patient. The average number of days per admission varied from fewer than 3 days to 1 week or more across all the health states. The average annual total cost per patient varied across all health states from approximately 170,000 to 600,000 baht, and medication cost was the largest portion in every cohort, except the HCV-related liver transplantation cohort in year 1. Among all medications, the average annual antiviral medication cost per patient was the largest portion in the noncirrhotic CHC and HCV-related compensated cirrhosis cohorts. Conclusions: CHC was a costly disease in Thailand. The average annual medication cost was the largest portion in every health state, except HCV-related liver transplantation. © 2013 International Society for Pharmacoeconomics and Outcomes Research (ISPOR).